Retinal hemoperfusion and vascular endothelial function after pancreatic transplantation - Evgeniy V. Bulava; Irina V. Vorobyova; Ilya V. Dmitriev; Aslan G. Balkarov (BMC Ophthalmology)
Abstract Introduction Ophthalmological assessment of the retinal circulation and the level of VEGF-A is currently considered a non-invasive and safe diagnostic tool to assess the peripheral microcirculation. Currently, there are few studies on the evaluation of retinal haemodynamics in patients with type 1 diabetes mellitus after pancreas transplantation, and we did not find any studies on the evaluation of VEGF-A levels in these patients. Materials and methods 79 patients (158 eyes) with type 1 diabetes mellitus and end-stage diabetic nephropathy participated in the study. Patients were divided into 3 groups: group 1, potential recipients of pancreas and kidney transplant from the waiting list; group 2, patients after kidney transplantation; and group 3, patients after simultaneous pancreas and kidney transplantation. Ophthalmological examination included measuring the macular hemoperfusion density. The level of VEGF-A was evaluated in the patients’ tear by enzyme immunoassay. Results Retinal hemoperfusion density and VEGF-A concentration were expected to correlate with the severity of diabetic changes in the fundus of patients. A lower index of retinal hemoperfusion density and a high level of VEGF-A were noted in patients with proliferative retinopathy and macular edema. Group 3 showed the lowest frequency of the active phase of the proliferative retinopathy and retinal macular edema, characterized by a higher retinal hemoperfusion density in the foveal and the parafoveal zone of the macular region, and low VEGF-A concentration in tear. Conclusions Evaluation of retinal hemoperfusion density and VEGF-A levels in tears are informative methods for diagnosing the severity of diabetic changes of the ocular fundus and for assessing the effect of restored physiological euglycaemia on the state of the peripheral circulation.